(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Although South Asia is geographically nearby and has bilateral and multilateral free trade agreements, it is one of the world’s least economically linked regions (FTAs). South Asia’s commerce is operating at a fraction of its capacity, accounting for just 5% of the region’s global trade as a consequence of protectionist laws, high logistical costs, a lack of political will, and an even wider trust gap. South Asia is one of the world’s most isolated areas, in comparison to other Asian and Pacific regions, where intra-regional commerce accounts for roughly half of overall trade. Assess India’s current degree of trade connectivity by examining developments in the country’s trade with its neighbours. The report concludes with a series of policy suggestions. Sri Lanka and Nepal, respectively, are India’s second and third largest regional export markets. Myanmar, Sri Lanka, and Bangladesh as a whole provide the vast bulk of the region’s imports. Bangladesh has a trade deficit with India of US7.6 billion, whereas Nepal has a trade deficit with India of US6.8 billion (2018). In recent years, the trade deficit has worsened. India’s overall trade with its neighbours has remained constant at between 1.7 and 3.8 percent.